Lecturer's teaching styles versus student's learning styles - a pilot study / Nurhidayah Masni Abdullah, Zakiyah Omar and Salimah Ahmad - Abdullah, Nurhidayah Masni; Omar, Zakiyah; Ahmad, Salimah (2009)
The purpose of this study is to investigate whether lecturer's teaching style complies with the student's learning style. A set of questionnaire based on Felder's four domains of Learning Style, namely, active-reflective, sensing-intuitive, visual-verbal and sequential-global was designed for data collection. The data were analysed using Microsoft Excel. The results show that the lecturers' teaching styles match the students' learning styles in three domains that are active reflective, visual-verbal and sequential-global but not in sensing-intuitive domain.